Theoretical considerations in cross-national employment research - Jacqueline O'Reilly (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1996)
This article critically reviews a range of theoretical approaches to cross-national employment research. It classifies these studies in terms of universal and culturalist perspectives. Universalists tend to ignore the concept of culture, or at best acknowledge it as a marginal phenomenon or additional variable. Culturalists, on the other hand, have sought to integrate the concept of culture into their analysis at a socio-economic and institutional level as well as at the psychological level of the individual. The emphasis on similarities between countries tends to lead to a universalist approach, whilst the emphasis on difference is often supported by a more culturalist perspective. This review highlights that the shortcomings of these approaches in terms of accounting for change and the co-existence of similarity and diversity. Further more, these studies, for the most part, are blind to the affects and effects of gender on industrial organisation and employment practices. – – In dem Beitrag werden theoretische Ansätze für international vergleichende Beschäftigungsstudien kritisch überprüft. Die Studien werden nach universalistischen und kulturalistischen Ansätzen unterschieden. Universalisten tendieren dazu, die Kategorie 'Kultur' zu ignorieren oder sie bestenfalls als ein marginales Phänomen oder eine zusätzliche Variable zu akzeptieren. Kulturalisten auf der anderen Seite haben versucht, in ihren Analysen das Kultur-Konzept auf einer sozioökonomischen, institutionellen und individualpsychologischen Ebene zu integrieren.
Keywords: 330